Depresión por endogamia en líneas S1 generadas de 14 poblaciones nativas de maíz harinoso (Journal on studies and research of academic knowledge, 2018)
The most used maize for human consumption in Paraguay is the floury type, commonly known as avatimorotî, which main hindrance is low yielding, due to the genetic material planted by small farmers, which grow this type of maize. Yield could be increased by using improved cultivars, mainly hybrid. To obtain superior hybrids, good lines are of paramount importance; thus, in the process of selecting lines to produce hybrids one of the aspects to be considered is the evaluation of inbreeding depression. As part of the aforementioned process, 14 landrace populations of floury maize were assessed for agronomical and productive characters to estimate inbreeding depression.  Landrace populations were subjected to self-pollination in 2016 and 2017. Experiments with 14 S0 populations and 64 S1 lines, varying in number per population, were conducted in a randomized complete block design with two replications, in out of season of 2018, at farmer field, in San Juan del Paraná district, Itapúa, Paraguay. Characters of cycle (male and female days to flowering), plant growth characters (ear and plant height), ear and kernel characters (lenght, number of kernel per hill and kernel percentage) and yield, were evaluated. Negative effects for selfingwere observed in both characters of cycle, increasing their values in the S1 generation.  Inbreeding depression values for plant growth and ear and kernel characters were lower than for yield, varying from 3.3% to 19.2%, with predominance of additive genetic effects. Inbreeding depression value for grain yield was 37.5%, with a higher participation of dominance effects.
Keywords: Floury maize; lines; genetic effects; yield